The Use Of Hermeneutics Double Movement Fazlur Rahman In Comprehending Hadith Of The Unsuccessful Leadership Of Women - Faiq Ainurrofiq (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This study examines the hadith about the failure of a nation when led by women. Textually, the meaning of the hadith is contrary to social reality that exhibits the number of women to become leaders in the political sphere. Using the contextual approach of double movement hermeneutics, Fazlur Rahman, this study compares textualist and contextualist methods in interpreting the hadith based on the meaning of the text and the historical, social and political context that underlie the emergence of the hadith. Based on the results of the study, it was found that the cause of a person's inability to be a leader was not because of his gender but because of lacking the capacity to be a leader. It can be found leaders who fail because they do not have leadership capacity, only with popularity, money, and political dynasties, and less capable in leadership. Lastly, this type of leader is addressed by the hadith, not the focus on gender